Increased Expression of the Mineralocorticoid Receptor in the Brain of Spontaneously Hypertensive Rats - Pietranera, Luciana (2012)
The mineralocorticoid receptor (MR) has been considered both neuroprotective as well as damaging for central nervous system function. MR may be also involved in central regulation of blood pressure. In the present study we compared the expression of MR and the glucocorticoid receptor (GR) in the hippocampus and hypothalamus of 16 weeks old spontaneously hypertensive rats (SHR) and the normotensive control WKY rats. In hippocampus, MR expression was studied by in situ hybridization (ISH), qPCR, and immunohistochemistry, whereas GR expression was analyzed by the last two procedures. Hypertensive animals showed increased expression of MR mRNA in whole hippocampus according to qPCR data and also in CA3 by ISH. Immunocytochemical staining for MR of dorsal hippocampus, however, did not show differences between SHR and WKY. SHR showed elevated hypothalamic MR mRNA by qPCR, and increased number of MR immunopositive cells in the magnocellular paraventricular region, compared to WKY. In contrast, expression levels of GR mRNA or protein in hippocampus and hypothalamus of SHR were similar to those of WKY rats. Furthermore, we further investigated the role of MR in the hypertensive rats by intracerebroventricular injection of the MR antagonist RU-2831 This compound produced a significant drop in blood pressure of SHR. In conclusion, MR expression is increased in the hippocampus and hypothalamus of SHR. We suggest that pathological MR overdrive may take responsibility for up regulation of blood pressure and the encephalopathy of hypertension.